Comparative Analysis Of Cordyceps Militaris Growth On Pearl Millet Substrate: Insights Into Morphology, Wet Weight, Dry Weight, And Cordycepin Level (International Journal of Environmental Sciences, 2025)
Cordyceps militaris, a valuable entomopathogenic fungus renowned for its medicinal properties, is gaining attention for its bioactive metabolite, cordycepin. This study investigates the growth performance and bioactive compound yield of C. militaris (DMRO-1163 strain) cultivated on pearl millet as a solid-state substrate. The cultivation was conducted under controlled conditions using a nutrient-enriched pearl millet medium. Morphological parameters including fruiting body length, wet and dry biomass, and cordycepin concentration were evaluated. The results indicated consistent and robust mycelial colonization within 10 days and the emergence of fruiting bodies between 20–25 days, with full maturity by 50–60 days. The average fruiting body length was 6.94 cm, with mean wet and dry weights of 27.43 g and 4.37 g per jar, respectively. Ultra High-Performance Liquid Chromatography (UHPLC) analysis revealed a cordycepin concentration of 5.965 mg/g in dried fruiting bodies. These findings highlight pearl millet as a cost-effective and efficient substrate for sustainable Cordyceps militaris cultivation, offering significant potential for pharmaceutical and nutraceutical applications.